HUBUNGAN REGULASI EMOSI DENGAN BLURRED REALITY BOUNDARIES PADA PEMAIN GAME GRAND THEFT AUTO ROLEPLAY DI SERVER EXECUTIVE ROLEPLAY - Gabriela Audrey; Riana Sahrani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The phenomenon of Grand Theft Auto V Roleplay has developed into an immersive digital space that allows players to construct virtual identities and engage in social interactions similar to those in the real world. This deep involvement can trigger blurred reality boundaries, a condition in which the distinction between real life and the game world becomes unclear. Emotion regulation plays an important role in helping players manage both their personal emotions and their characters’ emotions during gameplay. This study aims to examine the relationship between emotion regulation and blurred reality boundaries among GTA V Roleplay players on the Executive Roleplay server.This research employed a quantitative correlational method involving 306 participants aged over 18 years who had been playing for at least one year. The instruments used were the Emotion Regulation Questionnaire–Short Form (ERQ-S) and the Game Experience Questionnaire (GEQ). Spearman correlation analysis revealed a positive and significant relationship between emotion regulation and blurred reality boundaries (r = 0.676, p < 0.001). This indicates that higher emotion regulation ability is associated with a greater tendency to experience immersive involvement that blurs the boundaries between reality and the game world.